Factors Forming Indonesian Customers’ Attitudes and Intention towards Sharia Banking Products Before and After the COVID-19 Pandemic - Prisila Damayanty; Heri Yanto; Shine Pintor Siolemba Patiro (Universitas Negeri Semarang, 2026)
The objective of the research is to uncover the factors shaping customer attitudes and intentions towards using Islamic banking products in Indonesia after the COVID-19 pandemic. A preliminary study identified the factors shaping attitudes, including bank image, social norms, and compliance with Sharia law. This study also revealed differences in Indonesian customers’ intentions towards using Islamic banking products before and after the COVID-19 pandemic. Data collection used an online survey involving 479 Islamic banking customers in Indonesia. Structural Equation Modeling (SEM) was used for data analysis. The results indicate that attitudes can predict Indonesian customers’ intentions towards using Islamic banking products. The most influential factor influencing Indonesian customers’ attitudes towards using Islamic banking products is social norms. This study demonstrates the importance of reference groups and bank image in shaping attitudes and intentions, suggesting that banks should leverage these aspects to expand their customer base. This study also provides insights into individual decision-making and the importance of a social approach for banks in advertising. By confirming all TPB-related hypotheses, the study empirically validates and extends multi-attribute attitude model, Theory of Reasoned Action, Theory of Planned Behavior in the context of Sharia banking adoption after a global crisis. It demonstrates those model theories are reliable and adaptable framework for explaining Islamic financial behavior in emerging markets and during periods of economic disruption.